2011
DOI: 10.1007/s00411-010-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal occupational exposure to ionizing radiation and birth defects

Abstract: So far, only a few studies investigated occupational exposure to ionizing radiation in pregnancy to cause birth defects (BDs). No association between BDs and ionizing radiation, although described for high-dose exposure, could ever be confirmed for employees, or specific job titles. Here, an explorative analysis of a prospective population-based birth cohort used to quantify the prevalence of BDs in infants between 1/2007 and 2/2008 is presented. An active examination of all livebirths by specially trained pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
10
1
Order By: Relevance
“…In contrast, we assessed maternal exposure based on mother's descriptions of their occupations, workplaces and job activities and included 442 case mothers and 186 control mothers with potential occupational exposure to IR. Thus, compared with Wiesel et al (), our study has a much larger sample size and less precise measurements of exposure, and we observed no association between potential maternal occupational exposure to IR and all NBDPS birth defects in aggregate (AOR, 0.88; 95% CI, 0.74–1.05).…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In contrast, we assessed maternal exposure based on mother's descriptions of their occupations, workplaces and job activities and included 442 case mothers and 186 control mothers with potential occupational exposure to IR. Thus, compared with Wiesel et al (), our study has a much larger sample size and less precise measurements of exposure, and we observed no association between potential maternal occupational exposure to IR and all NBDPS birth defects in aggregate (AOR, 0.88; 95% CI, 0.74–1.05).…”
Section: Discussioncontrasting
confidence: 65%
“…A population‐based study of the association between occupational exposure to IR and birth defects was recently conducted in Germany (Wiesel et al, ). Based on a prospective follow‐up of 3816 pregnancies, Wiesel et al () observed that mothers who reported wearing a dosimeter during early pregnancy were 3.2 times more likely to have an infant affected by any type of birth defect (AOR, 3.2; 95% CI, 1.2–8.7) compared with mothers without occupational exposures to IR. However, only 29 women in their study reported wearing a dosimeter and of these only 4 had an infant with a birth defect (ventricular septal defect, hydronephrosis, ectopic kidney, and microtia/auricular artesian).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brent 1999; Cech et al 2007; Dekaban 1968; Feschchenko et al 2002; Green et al 2002; Plummer, 1952; Wiesel et al 2011). Defect categories with significant associations in multiple papers (not always consistently) included chromosomal defects such as Down syndrome, central nervous system / eye, oral clefts, skeletal defects, and heart defects.…”
Section: Discussionmentioning
confidence: 99%